Risk Factors of Type 2 Diabetes Mellitus in Pulmonary Tuberculosis Patients at Prof. Dr. Chairuddin P. Lubis Hospital USU - Neny Pristiwati Harahap; R Lia Kusumawati; Noni Novisari Soeroso; Santi Syafril; Gema Nazri Yanni (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Background: Diabetes mellitus (DM) and tuberculosis (TB) are major global health concerns with a bidirectional relationship that exacerbates clinical outcomes. Indonesia faces a high prevalence of both diseases; however, specific risk factors contributing to the incidence of Type 2 DM (T2DM) among pulmonary TB patients remain underexplored, particularly in North Sumatra. This study aims to identify risk factors associated with T2DMin patients with pulmonary TB. Method: A retrospective case-control study was conducted involving 80 participants, comprising 40 pulmonary TB patients with T2DM and 40 without DM. Data were obtained from electronic medical records and analyzed using Chi-square tests, Fisher’s Exact Test, and multivariate logistic regression. Result Educational level (OR = 5.001; p = 0.027), occupational status (OR = 3.500; p = 0.038), and nutritional status based on body mass index (OR = 3.498; p = 0.017) were significantly associated with the incidence of T2DM in pulmonary TB patients. Result: No significant associations were found for age, gender, radiographic findings, or smoking habits. Higher educational level, employment in the private sector, and having a normal to overweight BMI are key risk factors for T2DM among pulmonary TB patients.